1985
DOI: 10.1901/jeab.1985.44-279
|View full text |Cite
|
Sign up to set email alerts
|

The Basis of Superstitious Behavior: Chance Contingency, Stimulus Substitution, or Appetitive Behavior?

Abstract: This research examined three explanations for the "superstitious" behavior of pigeons under frequent fixed-time delivery of food: accidental response-reward contingency, stimulus substitution, and elicited species-typical appetitive behavior. The behavior observed in these studies consisted of occasional postfood locomotion away from the food hopper, and a predominant pattern of activity directed toward the hopper wall (wall-directed behavior), including approaching, stepping side to side, scratching with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
116
3
9

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(137 citation statements)
references
References 28 publications
9
116
3
9
Order By: Relevance
“…The approach described by Timberlake (1983a) and Timberlake and Lucas (1985) would appear to be more consistent with the present results. Their behaviorsystem view predicts that the type and rate of behaviors that arise in response to scheduled uess will depend on the behavioral conglomerate activated by the ues used.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The approach described by Timberlake (1983a) and Timberlake and Lucas (1985) would appear to be more consistent with the present results. Their behaviorsystem view predicts that the type and rate of behaviors that arise in response to scheduled uess will depend on the behavioral conglomerate activated by the ues used.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, the findings of this experiment are usefully viewed from the behavior-system perspective (Timberlake, 1983a;Timberlake & Lucas, 1985). Intermittent food presentations activate food-related foraging patterns.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Timberlake and Lucas (1985) in our work on the superstition paradigm proposed that the dominant responses of pressing against the wall and head bobbing in the absence of overt predictive stimuli could provide a ground for keypecking, especially because it appeared related to early niche-related behavior of begging crop-milk and food from adults. In support of this proposal, we have shown that ring doves (a congener of pigeons also feeding crop milk) show similar walldirected 'superstitious' behavior, while chickens show scratching and pecking the floor.…”
Section: A Brief Sur6ey Of Face-6alid Niche-related Aspects Of Generamentioning
confidence: 94%